2016
DOI: 10.1111/vde.12285
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of proactive long‐term maintenance therapy of canine atopic dermatitis with 0.0584% hydrocortisone aceponate spray: a double‐blind placebo controlled pilot study

Abstract: Background -Long-term remission between flares of canine atopic dermatitis (CAD) can be difficult to achieve. Therefore, additional strategic forms of treatment are needed in order to target flare prevention. The concept of proactive therapy is recommended in the European guidelines for the treatment of human atopic eczema.Objectives -To evaluate the efficacy of a proactive treatment regimen with a 0.0584% hydrocortisone aceponate (HCA) spray for CAD. Animals -Client-owned dogs with spontaneous atopic dermatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
0
21
0
2
Order By: Relevance
“…Although these results cannot be compared directly because of differences in canine populations and study designs, the TTF that we observed after lokivetmab proactive therapy seems to be about twice that seen without any treatment, but only half that obtained with twice‐weekly proactive topical glucocorticoid therapy . Furthermore, we compared our post‐lokivetmab Kaplan–Meier TTF curve with those of the HCA proactive study using a partial dataset provided by the authors of that study; the TTFs after lokivetmab therapy were significantly longer than those after placebo but not after the HCA (data not shown). We suspect that, compared to the topical HCA, the lower median TTF seen after lokivetmab is likely due to both a broader anti‐allergic effect of the glucocorticoid and a limited role of IL‐31 in the inflammation of atopic skin.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Although these results cannot be compared directly because of differences in canine populations and study designs, the TTF that we observed after lokivetmab proactive therapy seems to be about twice that seen without any treatment, but only half that obtained with twice‐weekly proactive topical glucocorticoid therapy . Furthermore, we compared our post‐lokivetmab Kaplan–Meier TTF curve with those of the HCA proactive study using a partial dataset provided by the authors of that study; the TTFs after lokivetmab therapy were significantly longer than those after placebo but not after the HCA (data not shown). We suspect that, compared to the topical HCA, the lower median TTF seen after lokivetmab is likely due to both a broader anti‐allergic effect of the glucocorticoid and a limited role of IL‐31 in the inflammation of atopic skin.…”
Section: Discussionmentioning
confidence: 90%
“…The median TTFs after placebo and HCA proactive therapy were 33 and 112 days, respectively . Although these results cannot be compared directly because of differences in canine populations and study designs, the TTF that we observed after lokivetmab proactive therapy seems to be about twice that seen without any treatment, but only half that obtained with twice‐weekly proactive topical glucocorticoid therapy . Furthermore, we compared our post‐lokivetmab Kaplan–Meier TTF curve with those of the HCA proactive study using a partial dataset provided by the authors of that study; the TTFs after lokivetmab therapy were significantly longer than those after placebo but not after the HCA (data not shown).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations